2022
DOI: 10.3856/vol50-issue1-fulltext-2762
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and serum chemistry profile in wild Pacific mackerel (Scomber japonicus) from Todos Santos Bay, Baja California, Mexico

Abstract: The Pacific mackerel Scomber japonicus aquaculture is receiving growing attention, and further development of this industry is expected to protect wild stocks. Information on S. japonicus hematology is very limited. Therefore, the present study aimed to provide the hematological and serum chemistry profiles associated with sex and some seasonal variations in Pacific mackerel from Todos Santos Bay, Baja California, Mexico. Fish were sampled in April (spring) and August (summer). Results showed that the conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(50 reference statements)
2
0
0
Order By: Relevance
“…The results showed that CF was always >1.4, so the setup does not compromise the health status of the fish. The current study also corroborates the CF result in the study of Vivanco-Aranda et al [41], wherein fish CF slowed down during summer compared to the spring with no statistical difference. The similarity could be attributed to the condition of the water temperature.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed that CF was always >1.4, so the setup does not compromise the health status of the fish. The current study also corroborates the CF result in the study of Vivanco-Aranda et al [41], wherein fish CF slowed down during summer compared to the spring with no statistical difference. The similarity could be attributed to the condition of the water temperature.…”
Section: Discussionsupporting
confidence: 92%
“…A similar result was found in mackerels, which gives lower results at low temperature [41]. Increased WBC counts throughout the summer and higher temperatures have been linked to infection caused by a number of diseases, indicating a fish protective response [41,45]. Nevertheless, in this study, no sign of disease was observed.…”
Section: Discussionsupporting
confidence: 85%